When the Audience Becomes the Storyteller: Role Identification and Emotional Experience in Interactive Films - Fan Zilin (SHS Web of Conferences, 2024)
This study delves into the phenomenon of audiences becoming storytellers within interactive films and its impact on role identification and emotional experience. By analyzing works such as Black Mirror: Bandersnatch, this paper reveals how interactive films provide a unique mode of narrative participation and, to some extent, redefine the relationship between audiences and films. The research finds that role identification and emotional experience in interactive films fundamentally differ from traditional films. The decision-making process in interactive films not only increases the sense of investment in the plot but also deepens identification with characters. However, this narrative form also presents challenges, including maintaining narrative coherence and balancing audience choice freedom with overall story quality. The study also discusses the complex impact of interactive films on audience emotional experience and offers suggestions for the future development of interactive films, including exploring new narrative techniques, targeted marketing strategies, technology integration, and the importance of personalized narratives. This paper provides new insights into understanding the impact and future development of interactive films and offers guidance for creators to produce more engaging and participatory interactive narrative works.